PDF تأثير الرياضة السياحية (التراثية) على الاقتصاد الوطني: تأثير الرياضة السياحية (التراثية) على الاقتصاد الوطني - خليفة سالمة الطيب خليفة (مجلة العلوم الرياضية والدراسات المرتبطة, 2025)
Abstract: The main objective of this study is to test the importance of tourism (heritage) sports on the national economy in Libya, using annual data covering the period from 1993 to 2018. To achieve this, a questionnaire and a standard model was designed based on economic theories and published scientific studies, and analysis methods and tests were used. The appropriate standard data, as for the data obtained, the financial budgets of the sports federations, the annual reports issued by the Olympic Committee, the General Sports Federations, the personal interview, the website of the World Bank (WB), and the Central Bank of Libya. The results of the standard analysis showed that attention to traditional industries, and the development and development of these industries necessarily requires improvement And the development of raw materials, competencies and manpower skills, the necessity of reviving the old heritage in the light of the new and making it intellectually and spiritually influential at the beginning of the renaissance of our new civilization, so that this revival stems from a comprehensive conception of the meaning of originality and a deep knowledge of the aspects of sports culture. and provide all means for that. Effective planning of the tourism sector works to develop it and achieve the objective function of the sector, which is to increase the public revenue by increasing non-oil revenues, which the researcher believes that the tourism sector can be one of the components of this revenue. Tourism has an effective impact on economic development, as well as affecting the foreign exchange earnings, and therefore there is a possibility that tourism will be a new source of national income. The growth of tourism activity is not alive, and it only comes according to careful planning of a strong and tight media program in which all media considerations are taken into account and through which all communication activities and various persuasive methods are used through a strong media apparatus, based on sound scientific foundations. In light of the findings, the study recommends the necessity of linking sports and tourism through sports tourism (recreational heritage) and has set up performances that express the civilizations that passed through Libya.